Body stores persist as fitness correlate in a long-distance migrant released from food constraints. (2nd July 2018) - Dokter, Adriaan M; Fokkema, Wimke; Bekker, Steven K; Bouten, Willem; Ebbinge, Barwolt S; Müskens, Gerard; Olff, Han; van der Jeugd, Henk P; Nolet, Bart A
Abstract : For geese preparing to fly to the Arctic, the motto is "the fatter the better." But, why do not all geese get fat when food is abundant? For brent geese, modern-day agricultural pastures turn out to be a land of plenty, where food harvesting is quick and leaves free time. But to enter the top tier of birds that produce offspring, other aspects like a good health may be more important than a pile of food. Abstract: Long-distance migratory birds rely on the acquisition of body stores to fuel their migration and reproduction. Breeding success depends on the amount of body stores acquired prior to migration, which is thought to increase with access to food at the fueling site. Here, we studied how food abundance during fueling affected time budgets and reproductive success. In a regime of plenty, we expected that 1) limitations on food harvesting would become lifted, allowing birds to frequently idle, and 2) birds would reach sufficient fuel loads, such that departure weight would no longer affect reproductive success. Our study system comprised brent geese ( Branta b. bernicla ) staging on high-quality agricultural pastures. Fueling conditions were assessed by a combination of high-resolution GPS tracking, acceleration-based behavioral classification, thermoregulation modeling, and measurements of food digestibility and excretion rates. Mark-resighting analysis was used to test for correlations between departure weight and offspring recruitment. Our results confirm that birds loafed extensively, actively postponed fueling in early spring, and took frequent digestion pauses, suggesting that traditional time constraints on harvest and fueling rates are absent on modern-day fertilized grasslands. Nonetheless, departure weight remained correlated with recruitment success. The persistence of this correlation after a prolonged stopover with access to abundant high-quality food, suggests that between-individual differences in departure condition are not so much enforced by food quality and availability during stopover, but reflect individual quality and longer-lived life-history traits, such as health status and digestive capacity, which may be developed before the fueling period.